2011
DOI: 10.1097/ftd.0b013e318203b41e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Performance of a Decision Support System to Improve Methotrexate Pharmacotherapy in Children and Young Adults With Cancer

Abstract: The management of high-dose methotrexate (MTX) therapy in patients with cancer depends on the routine monitoring of drug exposures in conjunction with leucovorin (LV), urine pH, patient hydration and other clinical indices of patient well-being. A key factor in patient oversight is the facilitation of MTX clearance in order to minimize drug-related toxicity. The aim of this investigation was to evaluate the performance of a clinical decision support system and Bayesian forecasting algorithm in the prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 53%
“…The former was the combination that had the weakest correlations in the present study, and the latter was the most frequently reported combination in previous studies. [9][10][11][12][13][14][15][16][17][18][19] As shown above, the sum of the absolute value of correlation coefficients among V 1 , k 10 , k 12 , and k 21 was 1.05 for regimen B, whereas V 1 , V 2 , CL, and Q was 3.29 for regimen B. Because of the relatively strong correlations among V 1 , V 2 , CL, and Q, this combination of the population parameters was considered to be a good target for a comparison with V 1 , k 10 , k 12 , and k 21 .…”
Section: Evaluation Of the Effect Of Correlations Among Population Pamentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling and simulation which represent the essential elements of pharmacometrics can be used in oncological drug development in selecting appropriate doses for clinical trials, optimizing trial designs, interpreting outcome data, or even predicting outcomes in settings which have not been explicitly studied (10). Pharmacometrics was also proven to be useful in individualizing clinical therapy in oncology and has been advocated for such a purpose (11)(12)(13)(14). This could be achieved based on the different covariates (such as gender, weight, mutational status of the patients, and/or others) which were found to significantly affect the outcome.…”
Section: Introductionmentioning
confidence: 99%